JUST IN TIME METHOD FOR RAW MATERIAL SUPPLY COST EFFICIENCY AT WISMA BATIK TRUSMI - Mekar Meilisa Amalia; Festus Evly R.I. Liow; Warkianto Widjaja; Fauzi Fauzi; Hendrik ES Samosir (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Study with a specific purpose This well-known just-in-time (JIT) technique of business increases efficiency, lowers costs, and ensures a smooth production process. Object investigation This is Wisma Batik Trusmi, which is located in the hamlet of Cinunuk subdistrict of Cileunyi district and operates in the sector of batik writing. For data analysis, quantitative analysis was employed as a method. Data is required for _cost computation, raw material supply, and application of the just-in-time approach. Primary data (in the form of report material raw production, inventory material raw, as well as cost material standard, and company history) and secondary data (in the form of literature from the library, notes during related lectures, books, and internet media theory that will be researched) are the types of data obtained.